2023
DOI: 10.3390/ijms24043783
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Deficiency and Supplementation in Sus scrofa Oocytes Influence Transcriptome Profiles in Oocytes and Blastocysts

Abstract: Mitochondrial DNA (mtDNA) deficiency correlates with poor oocyte quality and fertilisation failure. However, the supplementation of mtDNA deficient oocytes with extra copies of mtDNA improves fertilisation rates and embryo development. The molecular mechanisms associated with oocyte developmental incompetence, and the effects of mtDNA supplementation on embryo development are largely unknown. We investigated the association between the developmental competence of Sus scrofa oocytes, assessed with Brilliant Cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 109 publications
(191 reference statements)
0
3
0
Order By: Relevance
“…Since we did not find differences in imprinted gene expression pattern between autologous and heterologous mtDNA supplementation, this is not associated with heterologous transfer, but primarily as a result of adding extra copies of mtDNA which likely results from the changes to the genomic balance imposed by extra copies of mtDNA being introduced into the oocyte at the time of fertilisation. We have shown that mtDNA supplementation improved parental allele-specific imprinted gene expression patterns in blastocysts compared to non-supplemented blastocysts [35]; however, it may not be sufficient to recover levels similar to naturally conceived pigs.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Since we did not find differences in imprinted gene expression pattern between autologous and heterologous mtDNA supplementation, this is not associated with heterologous transfer, but primarily as a result of adding extra copies of mtDNA which likely results from the changes to the genomic balance imposed by extra copies of mtDNA being introduced into the oocyte at the time of fertilisation. We have shown that mtDNA supplementation improved parental allele-specific imprinted gene expression patterns in blastocysts compared to non-supplemented blastocysts [35]; however, it may not be sufficient to recover levels similar to naturally conceived pigs.…”
Section: Discussionmentioning
confidence: 84%
“…We have previously shown that allele-specific imprinted gene expression patterns were different between blastocysts generated with and without mtDNA supplementation [35]. We also demonstrated that single nucleotide polymorphism (SNP) frequency, calculated by SNP number divided by transcript length (kb), can be used as an indicator of mono-allelic or bi-allelic expression of genes at low and high frequency, respectively.…”
Section: Imprinted Genes Are Differentially Expressed In Mtdna-supple...mentioning
confidence: 99%
See 1 more Smart Citation